Efektivitas Model Discovery Learning dan Model Simulasi terhadap Kemampuan Analisis Matematis Siswa Kelas X - Widiastuti, Eni; Hidayat, Tomi; Ramadianti, Winda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the differences in mathematical analysis abilities of students learning through Discovery Learning, simulation, and conventional methods in mathematics learning for grade 10 at SMA Negeri 7, Bengkulu City. The research method used was quasi-experimental. Based on the results of SPSS calculations, it can be concluded that there is an analytical effect of using the Discovery Learning model on students' abilities in mathematics learning for grade 10 at SMA Negeri 7, Bengkulu City. This is evidenced by the calculated t value = 2.921 with a significance value of 0.004 <0.05 and a significance level of 5% for a two-tailed test and df = n - 2 - 1 = 65. The t table obtained is 1.98. Therefore, it can be concluded that t = 2.921 > t = 1.98, which means that there is a significant partial effect of the Discovery Learning model on students' analytical abilities at SMA Negeri 7, Bengkulu City. In conclusion, the Discovery Learning model (X1) and the simulation method (X2) have an effect on students' analytical abilities (Y). Keywords: Analysis, Discovery Learning, Simulation,